2016
DOI: 10.18632/oncotarget.11940
|View full text |Cite
|
Sign up to set email alerts
|

The putative oncotarget CSN5 controls a transcription-uncorrelated p53-mediated autophagy implicated in cancer cell survival under curcumin treatment

Abstract: Curcumin has shown promise as a safe and specific anticancer agent. The COP9 signalosome (CSN) component CSN5, a known specific target for curcumin, can control p53 stability by increasing its degradation through ubiquitin system. But the correlation of CSN5-controlled p53 to anticancer therapeutic effect of curcumin is currently unknown. Here we showed that CSN5-controlled p53 was transcriptional inactive and responsible for autophagy in human normal BJ cells and cancer HepG2 cells under curcumin treatment. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Phytochemicals including resveratrol, curcumin, and EGCG inhibit the proliferation of cancer cells by inducing autophagy . We examined whether UA induced autophagy in Ca922 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemicals including resveratrol, curcumin, and EGCG inhibit the proliferation of cancer cells by inducing autophagy . We examined whether UA induced autophagy in Ca922 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals including resveratrol, curcumin, and EGCG inhibit the proliferation of cancer cells by inducing autophagy. [32][33][34] We examined whether UA induced autophagy in Ca922 cells. As shown in Figure 4A, acidic organelles were stained by acridine orange after 24 hours of UA exposure.…”
Section: Ua Induces Autophagy In Osccmentioning
confidence: 99%
“…Our results indicate that CSN1 does not cooperate with IFT20 in the regulation of TCR trafficking to the IS but do not rule out a role for this protein in signalling events downstream of TCR stimulation. Recent evidence has implicated the COP9 signalosome in another critical quality control pathway, namely, autophagy (Pearce et al, 2009;Su et al, 2011;Zhang et al, 2016). Remarkably, the IFT system has been shown to participate in the first steps of autophagosome formation in ciliated cells (Pampliega et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have demonstrated the capability of p53 to induce autophagy; activation of p53 can cause excess autophagy in cancer cells (2527). However, inhibition of p53 has also been reported to enhance autophagy under environmental stress conditions (28). Therefore, the present study hypothesized that PEDF may induce excess autophagy via p53 to induce HUVEC death, which may prevent the progression of atherosclerotic plaque formation and tumor growth.…”
Section: Discussionmentioning
confidence: 99%